Clinical relevance of thiopurine methyltransferase genotype testing for azathioprine in dermatology - Ramassamy, Sivaranjini; Chandrashekar, Laxmisha; Mathaiyan, Jayanthi; Rajappa, Medha; Devanathan, Reka; Selvarathinam, Sujeevan; Goud, Alladi Charanraj (Clinical and experimental dermatology, 2025)
BACKGROUND: Polymorphisms in thiopurine methyltransferase (TPMT) are a predominant cause of azathioprine-induced leucopenia in Western countries. The exact role of these polymorphisms in the Indian population with dermatological disorders is uncertain. OBJECTIVES: To evaluate the frequency of genetic polymorphism of TPMT and its impact on the safety of azathioprine in dermatological disorders. METHODS: We included consecutive patients on azathioprine who were initiated for dermatological disorders from South India. Three TPMT polymorphisms (c.238G>C, c.460G>A and c.719A>G) were assessed. The proportions of adverse events to azathioprine, especially myelosuppression, were compared between those with the wildtype genotype and those with TPMT polymorphisms. RESULTS: Of the 123 patients (61 male and 62 female, mean age 46 years), 65% had an autoimmune blistering disorder. Adverse events to azathioprine were noted in 25 (20.3%), of whom 16 (13.0%) had myelosuppression and 4 (3.2%) each had hepatotoxicity and gastrointestinal intolerance. TPMT polymorphisms were detected in 13 (10.6%), of whom 5 had experienced adverse events. The polymorphisms could explain 25% (4 of 16) of the cases of leucopenia. The odds of developing leucopenia in patients with TPMT polymorphism were not significant (odds ratio 3.63, 95% confidence interval 0.96-13.6; P = 0.06). CONCLUSIONS: The tested TPMT polymorphisms could not predict the adverse events of azathioprine, particularly the haematological toxicity, in dermatological use among the South Indian population.
Keywords: Young Adult; kožní nemoci; Male; methyltransferasy; Immunosuppressive Agents; Skin Diseases; Genotype; mladý dospělý; polymorfismus genetický; Adolescent; Indie; Adult; Aged; dospělí; mužské pohlaví; senioři; Leukopenia; Clinical Relevance; India; Polymorphism, Genetic; mladiství; lidé; ženské pohlaví; Humans; azathioprin; Methyltransferases; genotyp; leukopenie; Female; Azathioprine; lidé středního věku; klinická relevance; imunosupresiva; Middle Aged